2017
DOI: 10.3748/wjg.v23.i28.5097
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic potential of flavonoids in inflammatory bowel disease: A comprehensive review

Abstract: The inflammatory process plays a central role in the development and progression of numerous pathological situations, such as inflammatory bowel disease (IBD), autoimmune and neurodegenerative diseases, metabolic syndrome, and cardiovascular disorders. IBDs involve inflammation of the gastrointestinal area and mainly comprise Crohn’s disease (CD) and ulcerative colitis (UC). Both pathological situations usually involve recurring or bloody diarrhea, pain, fatigue and weight loss. There is at present no pharmaco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
109
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(114 citation statements)
references
References 170 publications
0
109
0
5
Order By: Relevance
“…Finally, several studies have explored he effects of epicathenin containing dark chocolate on mitochondrial activity, with intriguing results 6. Although the study of Coe et al is an exploratory trial, it adds further interesting suggestions to the possible positive effects of flavonoid intake on the management of fatigue in patients with MS. A well designed, randomised, controlled, long term study with clinically meaningful endpoints is needed to clarify the potential benefits of flavonoid enriched chocolate to treat MS related fatigue.…”
Section: Preliminary Results From a Feasibility Study Suggest A Potenmentioning
confidence: 99%
“…Finally, several studies have explored he effects of epicathenin containing dark chocolate on mitochondrial activity, with intriguing results 6. Although the study of Coe et al is an exploratory trial, it adds further interesting suggestions to the possible positive effects of flavonoid intake on the management of fatigue in patients with MS. A well designed, randomised, controlled, long term study with clinically meaningful endpoints is needed to clarify the potential benefits of flavonoid enriched chocolate to treat MS related fatigue.…”
Section: Preliminary Results From a Feasibility Study Suggest A Potenmentioning
confidence: 99%
“…Most interest has been directed towards the antioxidant activity of flavonoids, evidencing a remarkable free-radical scavenging capacity. Flavonoids have many other biological properties, including anti-inflammatory, antiviral, anticancer, and neuroprotective activities [102]. Key mechanisms relate to their anti-inflammatory and antioxidant properties, as well as their ability to modulate gut microbiota, have been recently described [103].…”
Section: Flavonoidsmentioning
confidence: 99%
“…Wang et al showed that 6-hydroxyflavone (21) and its derivatives could potentially inhibit the downstream iNOS expression in kidney mesangial cells [28]. Luteolin (20), a natural flavone known as potent anti-inflammatory agent, found in many plant species, indicated to reduce TNF-α and proinflammatory cytokines expression, including that of TNF-α, IL-6 and IL-1β in RAW264.7 [29]. Apigenin (19) is a multitarget compound with promising anti-inflammatory activity.…”
Section: Investigation Of Anti-inflammatory Activity Of Subfractionsmentioning
confidence: 99%